Initiation and duration of breastfeeding of Aboriginal infants in South Australia. Issue 3 (June 2019) - Brown, Stephanie; Stuart-Butler, Deanna; Leane, Cathy; Glover, Karen; Mitchell, Amanda; Deverix, Janiene; Francis, Theresa; Ah Kit, Jackie; Weetra, Donna; Gartland, Deirdre; Yelland, Jane
Abstract: Background: Benefits of breastfeeding are well-established. Few studies have examined initiation and duration of breastfeeding of Aboriginal infants. Methods: Population-based study of women giving birth to an Aboriginal infant in South Australia, July 2011–June 2013. Findings: 344 women took part. Participants were representative in relation to maternal age, infant birthweight and gestation. Eighty-six percent initiated breastfeeding, declining to 54% at 12 weeks postpartum. Women living in remote areas were more likely to be breastfeeding at 12 weeks than women living in Adelaide (Odds Ratio = 2.6, 95% Confidence Interval 1.5–4.7). Two-thirds of women (67%) attending standard public antenatal care in regional areas and 61% attending regional Aboriginal Family Birthing Program Services were breastfeeding at 12 weeks, compared to one third of women (36%) attending standard metropolitan public antenatal care and 49% of women attending metropolitan Aboriginal Family Birthing Program Services. Less than half of women (45%) described their postnatal care as 'very good', and 40% were not always able to access support with infant feeding when needed. The most common reasons for switching to formula before 6 weeks were: low milk supply/baby not gaining weight, mastitis/sore breasts or other feeding problems. Mothers also identified their own health as a factor. Conclusion: While the findings must be treated with caution due to small numbers, they suggest benefits for women attending Aboriginal Family Birthing Program services in the urban environment where rates of initiation and continued breastfeeding are lowest. Provision of culturally appropriate support to Aboriginal women during and after pregnancy is key to improving outcomes.